UJI TOKSISITAS AKUT DAN SUB KRONIS RAMUAN JAMU UNTUK FIBRO ADENOMA MAMMAE (FAM) - Saryanto Saryanto; Danang Ardiyanto (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Mammary fibroadenomas (FAM) is the mammary gland benign tumor and has a high incidence rate in women aged 20-30 years. The purposes of this study are to assess the acute and subchronic toxicity of the herbs for FAM. The herb for FAM is a mixture of several simplisia (Curcuma zedoaria Rosch. rhizome; Loranthus parasiticus; Curcuma mangga Val. rhizome and Mammeria mimosa tuber) with a (10 g: 10 g: 5 g: 8 g: 7 g) ratio. Acute toxicity assay performed on the male and female Spraque-Dawley (SD) rats (aged 2-3 months with 200-250 g body weight). Forty-eight rats divided into four treatment groups (control group and three treatment groups of herbs for FAM). A decoction of herbs for FAM treated once a day orally. Toxicity clinical symptoms and lethal doses (LD50) observed for 7-14 days. Subchronic toxicity assay was also conducted in the male and female SD rats (aged 1.5-2 months with 150-200 g body weight). The three-dose series of herbs for FAM treated to the rats orally once daily for 90 days. The results of acute and subchronic toxicity assays found the quasi LD50 value of herbs for FAM is 5.000 mg/kg BW. This herb is safe for use in the medium term as an herbal medicine for FAM. Key words: FAM, acute, subchronic, toxicity assay